Removal of MuRF1 increases muscle mass in nemaline myopathy models, but does not provide functional benefits - Lindqvist, Johan; Kolb, Justin; de Winter, Josine; Tonino, Paola; Hourani, Zaynab; Labeit, Siegfried; Ottenheijm, Coen; Granzier, Henk (International journal of molecular sciences, 2022)
Nemaline myopathy (NM) is characterized by skeletal muscle weakness and atrophy. No curative treatments exist for this debilitating disease. NM is caused by mutations in proteins involved in thin-filament function, turnover, and maintenance. Mutations in nebulin, encoded by NEB, are the most common cause. Skeletal muscle atrophy is tightly linked to upregulation of MuRF1, an E3 ligase, that targets proteins for proteasome degradation. Here, we report a large increase in MuRF1 protein levels in both patients with nebulin-based NM, also named NEM2, and in mouse models of the disease. We hypothesized that knocking out MuRF1 in animal models of NM with muscle atrophy would ameliorate the muscle deficits. To test this, we crossed MuRF1 KO mice with two NEM2 mouse models, one with the typical form and the other with the severe form. The crosses were viable, and muscles were studied in mice at 3 months of life. Ultrastructural examination of gastrocnemius muscle lacking MuRF1 and with severe NM revealed a small increase in vacuoles, but no significant change in the myofibrillar fractional area. MuRF1 deficiency led to increased weights of various muscle types in the NM models. However, this increase in muscle size was not associated with increased in vivo or in vitro force production. We conclude that knocking out MuRF1 in NEM2 mice increases muscle size, but does not improve muscle function.